On the human appropriation of wetland primary production - James E. Cloern; Samuel M. Safran; Lydia Smith Vaughn; April Robinson; Alison Whipple; Katharyn E. Boyer; Judith Z. Drexler; Robert J. Naiman; James L. Pinckney; Emily R. Howe; Elizabeth Canuel; J. Letitia Grenier (Science of the Total Environment, 2021)
Humans are changing the Earth's surface at an accelerating pace, with significant consequences for ecosystems and their biodiversity. Landscape transformation has far-reaching implications including reduced net primary production (NPP) available to support ecosystems, reduced energy supplies to consumers, and disruption of ecosystem services such as carbon storage. Anthropogenic activities have reduced global NPP available to terrestrial ecosystems by nearly 25%, but the loss of NPP from wetland ecosystems is unknown. We used a simple approach to estimate aquatic NPP from measured habitat areas and habitat-specific areal productivity in the largest wetland complex on the USA west coast, comparing historical and modern landscapes and a scenario of wetland restoration. Results show that a 77% loss of wetland habitats (primarily marshes) has reduced ecosystem NPP by 94%, C (energy) flow to herbivores by 89%, and detritus production by 94%. Our results also show that attainment of habitat restoration goals could recover 12% of lost NPP and measurably increase carbon flow to consumers, including at-risk species and their food resources. This case study illustrates how a simple approach for quantifying the loss of NPP from measured habitat losses can guide wetland conservation plans by establishing historical baselines, projecting functional outcomes of different restoration scenarios, and establishing performance metrics to gauge success.